Kenny Music Performance Anxiety Inventory (K-MPAI-R): Confirmatory factor analysis of the Ukrainian version - Ksondzyk , Olena (Psychological Prospects Journal, 2020)
Purpose. Рerformance anxiety is one of the most central psychological problems in the professional activity of musicians. However, in Ukrainian clinical practice and research there is a lack of valid tools to assess it. This publication presents the results of psychometric analysis of the Ukrainian version of K-MRAI-R (revised Kenny Music Performance Anxiety Inventory). Based on Barlow’s theory of anxiety desorders, this measure assesses cognitive, affective, physiological and behavioral symptoms of music performance anxiety and its etiological aspects. The purpose of this study was to confirm the factor structure through a confirmatory factor analysis and determine its reliability by the Cronbach’s alpha criterion. Methodology. The study involved Ukrainian tertiary music students and professional musicians (age 18-72, M = 35.32, SD = 13.28; 63% women and 37% men) from different regions of Ukraine. Results: Results showed that the Ukrainian version of K-MRAI-R consisted of high psychometric indicators, validated through a confirmatory factor analysis. CFA did not support either of the two-, three- or eight-factor solutions. After excluding psychometrically poor items modified six-factor model proved to be a satisfactory fit (χ²/df = 1.75; CFI = 0.940 і TLI = 0.931; RMSEA =0.047; SRMR = 0.048). The high internal reliability of the questionnaire scales was confirmed by the Cronbach’s alpha (a good level for sub-scales «рroximal somatic anxiety» (.864), «worry/dread (negative cognitions) (.818), «depression/hopelessness» (.742), «anxious apprehension» (.839), and an acceptable level for sub-scales «рarental empathy» (.645), «generational transmission of anxiety» (.658). Conclusions. The Ukrainian version of K-MPAI-R may be used as a reliable and valid psychodiagnostic tool to provide diagnostical care and research music performance anxiety. Prospects for further research of the Ukrainian version of K-MRAI-R are to verify its convergent and divergent validity, test-retest reliability.